(untitled) (Revue El-Wahat pour les Recherches et les Etudes, 2026)
This research paper highlights the importance of civil protection for well-known trademarks, given that they are often subject to infringements and violations, particularly when they are not registered. a well-known trademark enjoys a wide reputation among consumers, which makes it vulnerable to exploitation, imitation, or confusion by third parties. in this context, both international conventions and national legislations have taken on the responsibility of ensuring adequate protection for this category of trademarks, whether officially registered or not. In this regard, the action for annulment of trademark registration occupies a central position in the legal framework protecting unregistered well-known marks. registration is not considered a prerequisite for initiating civil protection measures when it comes to well-known marks. accordingly, the owner of a well-known trademark — even if it has not been filed — is entitled to bring a legal action to annul the registration of any similar mark that may cause confusion or mislead the public, in order to safeguard their rights and the distinctiveness of their brand in the market.